FDI Promotion through Bilateral Investment Treaties More Than a Bit - Matthias Busse; Jens Königer; Peter Nunnenkamp (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Policymakers in developing countries have increasingly pinned their hopes on bilateral investment treaties (BITs) in order to improve their chances in the worldwide competition for foreign direct investment (FDI). However, the effectiveness of BITs in inducing higher FDI inflows is still open to debate. It is in several ways that we attempt to clarify the inconclusive empirical findings of earlier studies. We cover a much larger sample of host and source countries by drawing on a previously unpublished dataset on bilateral FDI flows. Furthermore, we account for unilateral FDI liberalization, in order not to overestimate the effect of BITs, as well as for the potential endogeneity of BITs. Employing a gravity-type model and various model specifications, including an instrumental variable approach, we find that BITs do promote FDI flows to developing countries. In addition, BITs are likely to act as a substitute for unilateral capital account liberalization.
Keywords: C33; F21; F23; 330; FDI; Multinational Corporations; Bilateral Investment Treaties